20 Years of the Eurasian Economic Integration - I. Novikova; V. Burkov; K. Mescheryakov (Евразийская интеграция: экономика, право, политика, 2019)
The article considers the evolution of the Eurasian economic integration in 1995-2015, describes its trends and problems, analyses its status in the context of worsening of the world political situation after the return of the Crimea and Sevastopol under Russia’s sovereignty.